2014
DOI: 10.1103/physrevlett.112.107002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Time-Reversal Symmetry Breaking in the Noncentrosymmetric SuperconductorRe6ZrUsing Muon-Spin Spectroscopy

Abstract: We have investigated the superconducting state of the noncentrosymmetric compound Re6Zr using magnetization, heat capacity, and muon-spin relaxation or rotation (μSR) measurements. Re6Zr has a superconducting transition temperature, Tc=6.75±0.05  K. Transverse-field μSR experiments, used to probe the superfluid density, suggest an s-wave character for the superconducting gap. However, zero and longitudinal-field μSR data reveal the presence of spontaneous static magnetic fields below Tc indicating that time-re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
212
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 184 publications
(242 citation statements)
references
References 36 publications
25
212
3
Order By: Relevance
“…SR data in the non-centrosymmetric superconductor ZrRe6, Tc=6.75 K, by Singh et al [581] showed spontaneous static magnetic fields below Tc, indicating (see section 2.1.8. above) breaking of time reversal symmetry.in the superconducting state, and UcS with strong singlettriplet pairing symmetry mixing. The specific heat =26 mJ/molK 2 [581], which is definitely not a highly correlated value, especially considering that six times the elemental  of Re plus the elemental  of Zr would (Stewart [19]) already be 16.5 mJ/molK Thus, non-centrosymmetric superconductors add two members (ZrRe6 and LaNiC2) to our list (B-phase UPt3, Sr2RuO4, PrOs4Sb12, and PrPt4Ge12) of UcS with time reversal symmetry breaking so far in this review, with the non-centrosymmetric ZrRe6 and the filled skutterudite PrPt4Ge12 having the largest Tc's (6.75 and 7.9 K respectively) by more than a factor of two.…”
Section: Low Correlation Asoc Induced Examplesmentioning
confidence: 90%
“…SR data in the non-centrosymmetric superconductor ZrRe6, Tc=6.75 K, by Singh et al [581] showed spontaneous static magnetic fields below Tc, indicating (see section 2.1.8. above) breaking of time reversal symmetry.in the superconducting state, and UcS with strong singlettriplet pairing symmetry mixing. The specific heat =26 mJ/molK 2 [581], which is definitely not a highly correlated value, especially considering that six times the elemental  of Re plus the elemental  of Zr would (Stewart [19]) already be 16.5 mJ/molK Thus, non-centrosymmetric superconductors add two members (ZrRe6 and LaNiC2) to our list (B-phase UPt3, Sr2RuO4, PrOs4Sb12, and PrPt4Ge12) of UcS with time reversal symmetry breaking so far in this review, with the non-centrosymmetric ZrRe6 and the filled skutterudite PrPt4Ge12 having the largest Tc's (6.75 and 7.9 K respectively) by more than a factor of two.…”
Section: Low Correlation Asoc Induced Examplesmentioning
confidence: 90%
“…The possibility of mixed spinsinglet spin-triplet pairing in noncentrosymmetric superconductors makes them prime candidates to exhibit TRS breaking 6 . To date, the only truly NCS reported to show TRS breaking are LaNiC 2 and Re 6 Zr, 16,21 however, for LaNiC 2 , a mixing of singlet and triplet states is forbidden due to the symmetry of the structure 22 27 and several have been shown to exhibit unconventional superconducting behavior including features such as upper critical fields close to the Pauli limit, evidence for multiple gaps, or a significant admixture of a triplet component to the superconducting order parameter. Muon spectroscopy studies have been performed on some of these compounds e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In weakly correlated transition metal compounds which do not exhibit magnetic complexity as in the heavy-fermion case, e.g., Ru 7 B 3 , AMSi 3 (A = Ca, Sr, La, and Ba and M = Co, Rh, Ir, Ni, Pd, and Pt), Mg 10 6 Zr, for which muon spin relaxation measurements reveal the presence of a spontaneous magnetic field below the critical temperature T c providing evidence for a superconducting state with time reversal symmetry breaking [22]. In the case of Nb x Re 1−x , measurements on polycrystalline samples with x = 0.18 confirm that it is a type-II superconductor with a bulk transition temperature T c ∼ 8.8 K [23,24].…”
Section: Introductionmentioning
confidence: 99%